149k views
5 votes
(11z2+4z-6)+(4z-7+12z2)+(-8+13z2+4z)​

User Ssegvic
by
5.8k points

2 Answers

6 votes

Answer:

huifytyjctrxrtfygvjhk

Explanation:

yeah he is right

User Jindra
by
6.4k points
5 votes

Answer:
36z^2+12z-21

Explanation:

You need to remember the multiplication of signs:


(+)(+)=+\\(+)(-)=-\\(-)(-)=+

In order to simplify the given the expression:


(11z^2+4z-6)+(4z-7+12z^2)+(-8+13z^2+4z)

You must distribute signs:


=11z^2+4z-6+4z-7+12z^2-8+13z^2+4z

And finally, you must add the like terms:


=36z^2+12z-21

User Ariso
by
7.2k points